Reproduction and Genetic Responsibility: An Interpretive Description of Reproductive Decision-Making for Young People With Li-Fraumeni Syndrome. (January 2022) - Forbes Shepherd, Rowan; Werner-Lin, Allison; Keogh, Louise A.; Delatycki, Martin B.; Forrest, Laura E.
The reproductive decision-making of young people (aged 15–39 years) with Li-Fraumeni syndrome (LFS), an early onset inherited cancer syndrome, has not been studied in depth. Using interpretive description methodology, we conducted semi-structured interviews with 30 young Australians (mean age 25.5 years) diagnosed with LFS or at 50% genetic risk. With reflexive thematic analysis, we show how young people's reproductive decision-making and ideals for family formation were shaped by a sense of genetic responsibility to ensure the health of future biological kin. Reproductive technology provided choices for family formation in the context of LFS and also complicated reproductive decisions, as these choices were difficult to understand, make, or carry out. We uphold that reproductive decision-making when living with LFS is a profoundly moral practice that may pose significant challenges for young people navigating their formative years. We offer genetic counseling practice recommendations to support individuals with LFS when making reproductive decisions.